Harmony Theory Course in Music University in China - Lei , Yan; Pattananon, Nicha (Journal of Roi Kaensarn Academi, 2024)
Music theory course is a basic course that students majoring in music performance must learn in colleges and universities. It includes a series of basic music theories such as basic music theory, harmony, music analysis, etc. For students majoring in music performance, they are not only theoretically rich, but also have some theoretical help for their own performance (singing). This paper briefly expounds the main content and current situation of music theory courses for students majoring in music performance in colleges and universities, so as to explore the importance of music ethics courses for students majoring in music performance, as well as the purpose and significance of learning. In China’s music colleges and universities, music harmony theory plays an important role in the basic teaching of composition and arrangement skills, and music majors need to learn harmony theory courses during college. This article presented harmony theory course in music university in China.